2023
DOI: 10.3390/cimb45030127
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Preconditioned Neural Stem Cell-Derived Extracellular Vesicles Contain Distinct Protein Cargo from Their Normal Counterparts

Abstract: Hypoxic preconditioning has been demonstrated to increase the resistance of neural stem cells (NSCs) to hypoxic conditions, as well as to improve their capacity for differentiation and neurogenesis. Extracellular vesicles (EVs) have recently emerged as critical mediators of cell–cell communication, but their role in this hypoxic conditioning is presently unknown. Here, we demonstrated that three hours of hypoxic preconditioning triggers significant neural stem cell EV release. Proteomic profiling of EVs from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…Despite NSC-derived EVs in vivo studies are very limited in number, in a few studies EVs isolated from NSC derived from iPSC and injected into rodents confirmed their role in neurodevelopment ( Cossetti et al, 2014 ) and in regulation of adult hippocampal neurogenesis ( Sullivan et al, 2015 ; Seguro et al, 2018 ; Gharbi et al, 2023 ). In particular, intranasal administration of EVs from human iPSC-derived NSCs into adult rodents demonstrated that they could target and get incorporated into neurons and glia in almost all brain regions, including the DG ( Gharbi et al, 2023 ). EV-treated rats displayed a higher density of Ki-67 + and DCX + /BrdU + cells in the SGZ suggesting that their cargo increases proliferation in the adult neurogenic niche ( Gharbi et al, 2023 ).…”
Section: Nspc-derived Evs: Role In Developmental and Adult Neurogenesismentioning
confidence: 99%
See 3 more Smart Citations
“…Despite NSC-derived EVs in vivo studies are very limited in number, in a few studies EVs isolated from NSC derived from iPSC and injected into rodents confirmed their role in neurodevelopment ( Cossetti et al, 2014 ) and in regulation of adult hippocampal neurogenesis ( Sullivan et al, 2015 ; Seguro et al, 2018 ; Gharbi et al, 2023 ). In particular, intranasal administration of EVs from human iPSC-derived NSCs into adult rodents demonstrated that they could target and get incorporated into neurons and glia in almost all brain regions, including the DG ( Gharbi et al, 2023 ). EV-treated rats displayed a higher density of Ki-67 + and DCX + /BrdU + cells in the SGZ suggesting that their cargo increases proliferation in the adult neurogenic niche ( Gharbi et al, 2023 ).…”
Section: Nspc-derived Evs: Role In Developmental and Adult Neurogenesismentioning
confidence: 99%
“…In particular, intranasal administration of EVs from human iPSC-derived NSCs into adult rodents demonstrated that they could target and get incorporated into neurons and glia in almost all brain regions, including the DG ( Gharbi et al, 2023 ). EV-treated rats displayed a higher density of Ki-67 + and DCX + /BrdU + cells in the SGZ suggesting that their cargo increases proliferation in the adult neurogenic niche ( Gharbi et al, 2023 ). Moreover, hiPSCs-NSCs derived EVs were enriched in proteins such as Agrin and pentraxin-3 previously shown to play a role in adult hippocampal neurogenesis ( Rodriguez-Grande et al, 2015 ; Zhang et al, 2020 ).…”
Section: Nspc-derived Evs: Role In Developmental and Adult Neurogenesismentioning
confidence: 99%
See 2 more Smart Citations